O conhecimento tradicional quilombola e suas interações com o uso dos recursos ambientais na Reserva Extrativista do Quilombo Frechal, município de Mirinzal-MA - Bernardes, Regina Helena (2006)
The Extractivist Reservation of Frechai Quilombo, located in the municipal district of Mirinzal - MA, represents a category of Conservation Unit that considers the permanency of the traditional population in the area who use the environmental resources through a self-sustainable way. The National System of Nature Conservation Units (SNUC) defines criteria and rules to use these resources through a participative administration, associated to the Plano of the Extractivist Reservation Use. The main objective of this work was analyzing the processes and practices associated to the traditional Quilombola knowledge and its implications in the use of environmental resources in a unit of categorized conservation as an Extractivist Reservation. The research was done through the application of questionnaires and semi-structured interviews to 82 families distributed in two communities: Rumo and Frechai, both located in the Extractivist Reservation. The Frechai community. for being characteristically compound by Quilombolas, was the main object of study on this research while the Rumo Community, whose dwellers are most Caboclos, was used as a comparative reference for the analysis of this. As to the ethnic topic, 83,67% of the population from the Frechai Community identified themselves as Negros while in the Rumo Community 87,88% identified themselves as Brunets. The economy of these communities is based on sustenance agriculture associated to extractivist activities through the combination of vegetable extractivism, represented mainly by the Babaçu coconut (Orbignya phalerata Mart.) and Açaí fruit (Euterpe oleracea Mart.), and the animal extractivism represented by handiwork fishing. In the agriculture, cassava (Manihot esculenta Crantz) represents the main alimentary and economic tillage, followed by the rice (Oryza sativa L.) and corn (Zea mays L.). The dwellers use several productive arrangements in the agricultural systems through pollytillages and monotillages. In the system of animal breeding, the families own the average of 17,13 poultries, 3,36 pigs and 3,18 cattles. In the backyards, the average amount of fruit species per family was 13,5 species. As to the knowledge about the Plan of Reservation Use in the Frechai Community, 61,2% of the interviewed declared that they had participated in the meetings where the creation of this plan was debated while in the Rumo Community, this percentage is 33,3%. The most problematic anthropic actions in the field are caused mainly by the population around the reservation and they refer to the predatory fishing, indiscriminate collection of açaí fruit and deforesting in permanent preservation area. At the moment, the populational increase in the reservation is also causing an increasing of pressure on the use of natural resources. In this work, we conclude that in the Extractivist Reservation, the Quilombolas from the Frechai community demonstrated to have a certain levei of more refined consciousness in the interactions with the use of environmental resources in relation to the dwellers of Rumo Community.